Aesthetics, Method, and Epistemology - Foucault, Michel 1926-1984; Faubion, James D. (London Penguin Books, 1994)
"Aesthetics" is the second in a three-volume, definitive collection of Michel Foucault's articles, interviews and seminars. It focuses primarily upon the philosophy, literature and other works of the imagination which have informed Foucault's particular engagement with ethics and power and includes Foucault's arresting commentaries on the work of de Sade, Rousseau, Marx, Nietzsche, Roussel and Boulez. 'A magnificent, essential compendium, in the absence of which the man, the thinker and his thought would have been amputated, unfinished and incompletely understood' - Liberation.
Keywords: Philosophy